Deletion of Polycomb Repressive Complex 2 From Mouse Intestine Causes Loss of Stem Cells - Koppens, Martijn A J; Bounova, Gergana; Gargiulo, Gaetano; Tanger, Ellen; Janssen, Hans; Cornelissen-Steijger, Paulien; Blom, Marleen; Song, Ji-Ying; Wessels, Lodewyk F A; van Lohuizen, Maarten (Gastroenterology (New York, N.Y. 1943), 2016)
The polycomb repressive complex 2 (PRC2) regulates differentiation by contributing to repression of gene expression and thereby stabilizing the fate of stem cells and their progeny. PRC2 helps to maintain adult stem cell populations, but little is known about its functions in intestinal stem cells. We studied phenotypes of mice with intestine-specific deletion of the PRC2 proteins embryonic ectoderm development (EED) (a subunit required for PRC2 function) and enhancer of zeste homolog 2 (EZH2) (a histone methyltransferase). We performed studies of AhCre;EedLoxP/LoxP (EED knockout) mice and AhCre;Ezh2LoxP/LoxP (EZH2 knockout) mice, which have intestine-specific disruption in EED and EZH2, respectively. Small intestinal crypts were isolated and subsequently cultured to grow organoids. Intestines and organoids were analyzed by immunohistochemical, in situ hybridization, RNA sequence, and chromatin immunoprecipitation methods. Intestines of EED knockout mice had massive crypt degeneration and lower numbers of proliferating cells compared with wild-type control mice. Cdkn2a became derepressed and we detected increased levels of P21. We did not observe any differences between EZH2 knockout and control mice. Intestinal crypts from EED knockout mice had signs of aberrant differentiation of uncommitted crypt cells-these differentiated toward the secretory cell lineage. Furthermore, crypts from EED-knockout mice had impaired Wnt signaling and concomitant loss of intestinal stem cells, this phenotype was not reversed upon ectopic stimulation of Wnt and Notch signaling in organoids. Analysis of gene expression patterns from intestinal tissues of EED knockout mice showed dysregulation of several genes involved in Wnt signaling. Wnt signaling was regulated directly by PRC2. In intestinal tissues of mice, PRC2 maintains small intestinal stem cells by promoting proliferation and preventing differentiation in the intestinal stem cell compartment. PRC2 controls gene expression in multiple signaling pathways that regulate intestinal homeostasis. Sequencing data are available in the genomics data repository GEO under reference series GSE81578; RNA sequencing data are available under subseries GSE81576; and ChIP sequencing data are available under subseries GSE81577.